Pengaruh Media Pembelajaran Interactive Multiplication Stacking Board terhadap Pemahaman Kognitif pada Operasi Hitung Perkalian Kelas III SD - Adjeng Putri Wahyoerie; Tasya Nurmadina; Kowiyah Kowiyah (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This research is based on the limited use of learning media among teachers, although the media is important to support 21st century learning that should utilize technology. The lack of special media for multiplication materials in grade III of elementary school causes learning to be less in line with the stage of cognitive development of students. Usually, teachers use lecture methods and multiplication tables, which makes students tend to only listen and memorize. As a solution, researchers developed the Interactive Multiplication Stacking Board media, which aims to facilitate the understanding of the concept of multiplication through the repeated multiplication approach so that students can understand the concept of multiplication concretely. This research aims to design, develop, and test the feasibility of the learning media. The method used is Design-Based Research with the Reeves model, which includes problem identification, prototype development based on relevant theories, as well as product testing and improvement through validity tests and repeated trials. The final result of this research is the Interactive Multiplication Stacking Board learning media that is ready to be used to support multiplication learning in class III in elementary school.